MENINGKATKAN KEMAMPUAN PEMAHAMAN DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK MELALUI TEKNIK SQ4R DAN PETA KONSEP SISWA SMP - Uba Umbara (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
This study used experimental design, and chose a research design in the form of pretest-posttest control group design. The subjects of this study were students Middle School, with the research sample being students of SMP Negeri 1 Kabupaten Kuningan which consists of two classes taken randomly. To obtain data research procedures are needed through three main stages, namely the preparation stage, the implementation phase in the class and the data analysis stage. After the data collected, the data were analyzed descriptively and inferentially. From the results of data analysis and The discussion concluded that (1) the quality of the ability of mathematical comprehension of junior high school students increases after students take mathematics learning using the SQ4R technique and the copsep map, (2) the problem solving abilities of junior high school students increase after students take mathematics learning using SQ4R techniques and concept maps, (3) there are significant differences in understanding abilities and mathematical problem solving abilities between students in mathematics learning using the SQ4R technique and concept maps with students in mathematical learning in the usual way; the ability of students in mathematics learning uses SQ4R techniques and concept maps are better than students who are deep mathematical learning in the usual way, (4) student attitudes support learning mathematics with SQ4R techniques and concept maps, and (5) teachers provide positive responses to mathematics learning using SQ4R techniques and concept maps